Studying the susceptibility of red flour beetles to penetration and control of some packaging materials using low pressure and carbon monoxide and nitrogen oxides - Ibraheem Al-Hadedi; Ayad Ismaeel (College of Education for Pure Sciences, 2007)
Ninevah province is one of the ancient places in Iraq in producing of wheat from which , in addition to flour , many products are prepared since the first thousand years BC . These products are subjecte to infestation with red flour beetle, Tribolium castaneum (Herbst ) & khapra beetie,Trogoderma granarium Everts. Hence, the present investigation aimed at studying the biology of both insects at 32±1 °C & relative humidity 70±5% . The control was 95% flour powder & 5% yeast powder. Results of the present study showed that Among the different types of pouches investigated, those made of polypropylene were found to be the most resistant to penetration , followed by aluminum foil. polyester . Cellophane. Polyethylene and gunny. Highest mortality rate of both insects was due to subjection to carbon dioxide ,followed by subjection to nitrogen gas and finally those subjected to low pressure. Sensitivity of different stages to these gases was as follows: adult> egg> pupa >larva. From the results of the above mentioned study, can be concluded that Low pressure, carbon dioxide or nitrogen can be employed to protect these products from infestation by the two insects studied .